Elucidation of Enzymatic Mechanism of Phenazine Biosynthetic Protein PhzF Using QM/MM and MD Simulations - Liu, Fei (PLoS One, 2015)
The phenazine biosynthetic pathway is of considerable importance for the pharmaceutical industry. The pathway produces two products: phenazine-1,6-dicarboxylic acid and phenazine-1-carboxylic acid. PhzF is an isomerase that catalyzes trans-2,3-dihydro-3-hydroxyanthranilic acid isomerization and plays an essential role in the phenazine biosynthetic pathway. Although the PhzF crystal structure has been determined recently, an understanding of the detailed catalytic mechanism and the roles of key catalytic residues are still lacking. In this study, a computational strategy using a combination of molecular modeling, molecular dynamics simulations, and quantum mechanics/molecular mechanics simulations was used to elucidate these important issues. The Apo enzyme, enzyme–substrate complexes with negatively charged Glu45, enzyme–transition state analog inhibitor complexes with neutral Glu45, and enzyme–product complexes with negatively charged Glu45 structures were optimized and modeled using a 200 ns molecular dynamics simulation. Residues such as Gly73, His74, Asp208, Gly212, Ser213, and water, which play important roles in ligand binding and the isomerization reaction, were comprehensively investigated. Our results suggest that the Glu45 residue at the active site of PhzF acts as a general base/acid catalyst during proton transfer. This study provides new insights into the detailed catalytic mechanism of PhzF and the results have important implications for PhzF modification.